Genetic and Morphological Diversity of Indigenous Bradyrhizobium Nodulating Soybean in Organic and Conventional Family Farming Systems - Gitonga, Nicholas Mawira; Njeru, Ezekiel Mugendi; Cheruiyot, Richard; Maingi, John M. (Frontiers in Sustainable Food Systems, 2021)
Organic farming systems are gaining popularity as agronomically and environmentally sound soil management strategies with potential to enhance soil microbial diversity and fertility, environmental quality and sustainable crop production. This work aimed at understanding the effect of organic and conventional farming on the diversity of soybean nodulating bradyrhizobia species. Field trapping of indigenous soybean Bradyrhizobium was done by planting promiscuous soybeans varieties SB16 and SC squire as well as non-promiscuous Gazelle in three organic and three conventional farms in Tharaka-Nithi County of Kenya. After 50 days of growth, 108 nodule isolates were obtained from the soybean nodules and placed into 13 groups based on their morphological characteristics. Genetic diversity was done by polymerase chain reaction (PCR) targeting 16S rDNA gene using universal primers P5-R and P3-F and sequencing was carried out using the same primer. High morphological and genetic diversity of the nodules isolates was observed in organic farms as opposed to conventional farms. There was little or no genetic differentiation between the nodule isolates from the different farms with the highest molecular variation (91.12%) being partitioned within populations as opposed to among populations (8.88 %). All the isolates were identified as bradyrhizobia with close evolutionary ties with Bradyrhizobium japonicum and Bradyrhizobium yuanminense. Organic farming systems favor the proliferation of bradyrhizobia species and therefore a suitable environmentally friendly alternative for enhancing soybean production.